Colon wall motility: comparison of novel quantitative semi-automatic measurements using cine MRI - Hoad, Caroline; Menys, A.; Garsed, Klara; Marciani, Luca; Hamy, Valentin; Murray, Kathryn; Costigan, Carolyn; Atkinson, D.; Major, Giles; Spiller, Robin C.; Taylor, S.; Gowland, Penny A. (Wiley, 2016)
Background